C4b-binding Protein Inhibits the Factor V-dependent but not the Factor V-independent Cofactor Activity of Protein S in the Activated Protein C-mediated Inactivation of Factor VIIIa - van de Poel, Robbert H. L.; Meijers, Joost C. M.; Bouma, Bonno N. (Thrombosis and Haemostasis, 2001)
Activated protein C (APC) is an important inactivator of coagulation factors Va and VIIIa. In the inactivation of factors Va and VIIIa, protein S serves as a cofactor to APC. Protein S can bind to C4b-binding protein (C4BP), and thereby loses its cofactor activity to APC. By modulating free protein S levels, C4BP is an important regulator of protein S cofactor activity. In the factor VIIIa inactivation, protein S and factor V act as synergistic cofactors to APC. We investigated the effect of C4BP on both the factor V-independent and factor V-dependent cofactor activity of protein S in the factor VIIIa inactivation using a purified system. Protein S increased the APC-mediated inactivation of factor VIIIa to 60% and in synergy with protein S, factor V at equi-molar concentrations increased this effect further to 90%. The protein S/factor V synergistic effect was inhibited by preincubation of protein S and factor V with a four-fold molar excess of C4BP. However, C4BP did not inhibit the factor V-independent protein S cofactor activity in the purified system whereas it inhibited the cofactor activity in plasma. We conclude that C4BP-bound protein S retains its cofactor activity to APC in the factor VIIIa inactivation.
Keywords: C4b-binding protein; protein S; factor VIII; protein C; factor V